The Role Of Health Information Management Professionals In Healthcare Administration. An Evolution (Journal of Namibian Studies : History Politics Culture, 2022)
Health information management (HIM) professionals play a crucial role in modern healthcare administration by serving as custodians of patient data, facilitating decision-making, driving quality improvement, ensuring regulatory compliance, supporting interoperability, advancing health information technology (HIT), and educating stakeholders. This abstract provides an overview of the multifaceted responsibilities of HIM professionals and their indispensable contributions to effective healthcare delivery.